Total systems design on Event Solutions - Castro, John Amar; Estadilla, Marc Joseph; Latagan, Salvacion; Obenita, Mylene
Event solution is a family-run business with over 15 years of supplying in different types of events. From their head office in Bocaue, Bulacan, they supply high quality dishes and operate catering units throughout the Greater Manila Area as well as Metro Manila. They provide services like food catering, photography and video coverage of the event, invitations, spotlights, clowns, hosting, etc. They also consolidate with other businesses so as to meet the demand of the client. They cater for all size of events and can offer the event organizer a range of solutions depending on the requirement of the event. Event Solutions is encountering problems in their operations attributable to lack of well-defined company goals, indistinct organizational structure and loose operational procedures which result to costs, time and effort. Costs are avoidable and opportunity costs. Avoidable costs are due to loose marketing efforts. To address the problem, the proponents cited recommendations on four major areas in the operations of the company namely, organizational framework, process standardization, information system and business strategies. These gour areas are perceived to be the most problematic. In improving the organizational framework, the company should introduce the new trademark and restructure the current organizational hierarchy. Company objectives should be set to have a consistent growth and observe appropriate management practices. It is also essential for the company to introduce the standard operating procedures. This will help the management to properly employ and document their tasks and processes and ensure that every product or service given to the clienteles is of prime quality. The installation of the information system will automate a few of the manual operations and provide an electronic database of their customers, events, suppliers and employees and also keep track of their financial records. Event solution should also intensify their marketing sites and available print advertisement. The implementation of the new system will have a cost of not greater than of approximately Php 100,000 is expected. However the benefits are far greater than the costs as the company's sales are expected to increase.